Estratégias interativas na educação online : estudo de caso nos fóruns do curso piloto de administração a distância do Sistema Universidade Aberta do Brasil em Maceió - AL - Lopes, Myllena Calheiros (2009)
This dissertation aims at the analysis of online interactions that influence the effectiveness of collaborative learning among participants of the forums on the environment and indexed-ProInfo Pilot Course Management Courses at the Open University of Brazil in Maceió-Alagoas. The methodology adopted to conduct the research was a qualitative type, in a case study approach and research techniques with systematic observation in the forums of course, the use of interviews and questionnaires to the working of the samples, and bibliographical studies based on Dillenbourg (1996), Mercado (2006, Silva (2006), Vygotsky (1979/1996), Yin (2005) among others. The type of sampling of the research was by events in the forums of the course, ie, the selection board was held in the presence of online collaborative interactions among students from four disciplines offered in the initial semesters of the course. For data analysis we selected four major samples, ie the selection of four forums with the presence of potential online collaborative interactions among students. Through analysis of the interview with the academic advisor of the four first semesters of the course was possible to rescue some clippings structuring the course, as functions of the major players in the forums of course, that is, the teacher and tutor students. For the analysis of questionnaires sent via conventional email and webmail e-Proinfo environment for teachers and students from selected samples of 11 teachers 0% returned the questionnaires, while 14% of the 85 students returned the survey instrument. For the analysis of selected forums, there are minimum collaborative online interactions between students, minimum collaborative online interactions of teachers to students and the presence of potential collaborative online interactions of students to teachers. Given the focus of the interactive process as a mechanism conducive to participation and the formalization of collaborative learning in data analysis was possible to identify possible indicators for the construction of collaborative learning in the forums of course investigated and possibly a contribution in courses offered in Education Online